The chocolate snowman murders - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery., 2008)
The much anticipated Winter Arts festival is here, and as treasurer of Winterfest, Lee is up to her elbows in mix-ups behind the scenes. When the art show's guest juror shows up drunk, Lee lets him sleep it off, only to find out later that someone's put the visiting dignitary into a permanent state of repose. Lee and Joe were the last people spotted near the crime scene. In a seriously sticky situation, it's up to them to find the real killer before someone else comes to a bitter end...